High-strength high-ignition-point magnesium alloy and preparation method thereof

CN118109731BActive Publication Date: 2026-10-27BAOSTEEL METAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211524480.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2026-10-27
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

[0011]本发明的目的在于提供一种高强高燃点镁合金及其制备方法,所述高强高燃点镁合金的抗拉强度≥280MPa,屈服强度≥250MPa,延伸率≥8%,燃点≥780℃;本发明解决现有的镁合金难以变形加工与耐高温性能较差的问题

Benefits of technology

[0052]本发明只需添加微量的Y元素,通过调控Ca/Y元素含量比值的方法,优化阻燃镁合金中Mg2Ca相的数量,从而实现合金力学性能与燃点的协同提升,得出本发明合金。想比于传统的阻燃镁合金具有材料成本低廉、可以满足大规模工程应用的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003972536600000081
    Figure BDA0003972536600000081
  • Figure BDA0003972536600000091
    Figure BDA0003972536600000091
  • Figure BDA0003972536600000092
    Figure BDA0003972536600000092
Patent Text Reader

Abstract

The high-strength high-ignition-point magnesium alloy and a preparation method thereof, the magnesium alloy comprises the following components in percentage by weight: Zn 5.10-6.30%, Al 0.50-1.00%, Mn 0.15-0.35%, Ca 1.50-2.50%, Y 0.50-1.00%, and the balance of Mg and other inevitable impurities, and meanwhile, the following conditions are met: Ca / Y=2-4; and the magnesium alloy is obtained by the following method, including: the cast ingot of the magnesium alloy is subjected to twice extrusion to obtain a finished product, the first extrusion ratio is 2-5, and the second extrusion ratio is 9-25. The high-strength high-ignition-point magnesium alloy has the following properties: tensile strength ≥280 MPa, yield strength ≥250 MPa, elongation ≥8%, and ignition point ≥780 DEG C. The present application solves the problems of poor high-temperature resistance and difficult deformation of the existing magnesium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnesium alloys, specifically relating to a high-strength, high-ignition-point magnesium alloy and its preparation method. Background Technology

[0002] Magnesium alloys, as the lightest metallic structural materials used in engineering applications, are 75% lighter than steel and 33% lighter than aluminum, earning them the title of "21st-century green engineering materials" and possessing enormous market potential. my country has extremely rich proven magnesium ore reserves, accounting for over 70% of the global total. Magnesium alloys exhibit excellent vibration damping performance, absorbing 1.5 times the energy of aluminum alloys and possessing damping properties more than ten times higher. They also have excellent machinability and are almost 100% recyclable. Magnesium alloys have a specific stiffness similar to aluminum alloys but a specific strength far exceeding that of aluminum alloys and steel, allowing them to absorb more impacts for the same mass. Therefore, magnesium alloys are highly promising structural materials.

[0003] Magnesium alloys are chemically highly reactive, resulting in poor corrosion resistance and flame retardancy. This poses safety hazards during material preparation and smelting. Magnesium is highly flammable due to its high surface activity, easily ignited by open flames or strong electric sparks, with combustion temperatures reaching 3000℃ to 5000℃. Its flammability must be carefully considered when considering the application of magnesium alloys, significantly limiting their application range. High-ignition-point magnesium alloys have always been a hot research topic in the field. Currently, aluminum alloys are the primary material for rail transit vehicle bodies, but magnesium alloys can further achieve lightweighting. Therefore, there is an urgent need to develop a high-strength, high-ignition-point wrought magnesium alloy.

[0004] Numerous studies have been conducted on high-ignition-point extruded magnesium alloys. Adding certain alloying elements can improve the alloy's strength and ignition point. For example:

[0005] Chinese Patent Application Publication No. CN109536798 discloses a flame-retardant magnesium alloy, its preparation method, and its application. The alloy's composition is: 6–8.9 wt% Al, 0.5–1.1 wt% Zn, 0.3–0.7 wt% Mn, 1.3–2.2 wt% Ca, 0.3–0.6 wt% Sr, 0.3–1.2 wt% Ce and / or Y, 0.01–0.2 wt% Nd, 0–0.05 wt% Be, with the balance being Mg and unavoidable impurities. Its room temperature tensile strength is 231–243 MPa, its yield strength is 171–185 MPa, and its ignition point is 660–750 °C. However, the alloy's mechanical properties and flame-retardant ability are poor, insufficient to meet the requirements of modern industrial and transportation applications.

[0006] Chinese patent application publication number CN108048720 discloses a flame-retardant magnesium alloy with added yttrium and calcium and its preparation method. The composition is: Mg 84.9-88.55%, Al 7.5-9.0%, Zn 0.2-0.8%, Mn 0.15-0.5%, Si 0.3%, Y 3.0-4.0%, and Ca 0.3-0.5%. The cost of this alloy is relatively high, with the price of rare earth Y ranging from 400 to 500 yuan / kg, making it difficult to meet the practical needs of large-scale engineering applications.

[0007] Chinese Patent Application Publication No. CN114438384 discloses a low-cost, high-strength, tough, and fire-resistant magnesium alloy and its extruded material preparation method. The chemical composition of the magnesium alloy by weight percentage is: Zn 0.5-2.5wt%, Ca 0.2-1.5wt%, Mn 0.1-0.5wt%, Sn 0.5-2.0wt%, Al 0.5-1.5wt%, Bi 0.2-1.8wt%, Sr 0.1-0.5wt%, with the remainder being Mg and other unavoidable impurities. The highest ignition temperature of this alloy composition is 725℃, which is relatively low and poses a safety hazard, making it difficult to meet the requirements of practical applications.

[0008] Chinese patent application publication number CN1540016 discloses a cast flame-retardant magnesium alloy with the following composition: 6.5-10% Al, 0.2-0.6% mixed rare earth elements, 0.1-1.5% Zn, 0.05-0.3% Mn, 0-0.02% Be, and the remainder being magnesium. The invention has a room temperature tensile strength of 175 MPa, an elongation of 7%, and an ignition point of 800°C. However, this patent does not involve deformation processing, resulting in poor mechanical properties, and its strength is insufficient to meet the requirements for use.

[0009] Chinese patent application publication number CN103526092 discloses a flame-retardant deformable magnesium alloy and its preparation method. The alloy's composition is: 1.0–6.0% Y, 0.05–1.5% Ca, 0.05–0.5% Ce, 0–0.5% Zr, with the remainder being magnesium. The preparation method involves a single extrusion molding process at an extrusion temperature of 250–450℃ and an extrusion ratio of 5–25. The invention exhibits a room temperature yield strength of 274 MPa, a tensile strength of 320 MPa, and an elongation of 12%. However, this patent utilizes a large amount of rare earth elements and employs a single extrusion molding process, resulting in high cost and low strength, making it difficult to meet application requirements.

[0010] These patents all describe adding certain alloying elements to increase the ignition point. Our research found that only when the metallic elements calcium and rare earth elements are within a certain proportion range can the ignition point of magnesium alloys be improved; outside this range, there is no significant improvement in increasing the ignition point. Other patents describe improving the mechanical properties of metallic materials through extrusion. Our research found that only when the extrusion ratio is within a certain range can the mechanical properties of the material be improved; outside this range, the mechanical properties actually decrease. Summary of the Invention

[0011] The purpose of this invention is to provide a high-strength, high-ignition-point magnesium alloy and its preparation method. The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃. This invention solves the problems of existing magnesium alloys being difficult to deform and process and having poor high-temperature resistance.

[0012] To achieve the above objectives, the technical solution of the present invention is as follows:

[0013] A high-strength, high-ignition-point magnesium alloy has the following composition by weight percentage: Zn 5.10–6.30%, Al 0.50–1.00%, Mn 0.15–0.35%, Ca 1.50–2.50%, Y 0.50–1.00%, with the balance being Mg and other unavoidable impurities, and simultaneously satisfying: Ca / Y = 2–4; and is obtained by the following method, comprising: extruding the magnesium alloy ingot twice to obtain the finished product, wherein the first extrusion ratio is 2–5 and the second extrusion ratio is 9–25.

[0014] Furthermore, the balance consists of Mg and other unavoidable impurities.

[0015] Preferably, the total mass fraction of unavoidable impurity elements in the high-strength, high-ignition-point magnesium alloy of the present invention is less than 0.2%.

[0016] Preferably, the Zn content is 5.50%–6.00%.

[0017] Preferably, Al is 0.55% to 0.80%.

[0018] Preferably, Mn is 0.20% to 0.30%.

[0019] Preferably, Ca is 1.80–2.30%.

[0020] Preferably, Y is 0.60% to 1.00%.

[0021] The microstructure of the high-strength, high-ignition-point magnesium alloy of the present invention consists of fine magnesium alloy grains, Mg2Ca phase dispersed at the grain boundaries, and fine MgZn2 phase inside the grains.

[0022] The high-strength, high-ignition-point magnesium alloy of the present invention has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

[0023] In the high-strength, high-ignition-point alloy composition design described in this invention:

[0024] Al is the most important alloying element in magnesium alloys. It can increase the boiling point of magnesium alloys. The high-strength, lightweight alloys obtained after alloying can be used as structural materials. Al can also improve the strength and hardness of alloys.

[0025] Mn has a similar effect to Al, significantly improving the tensile strength of magnesium alloys by forming a second phase. In Al-containing magnesium alloys, the solid solubility of Mn is less than 0.3%. In addition, Mn can refine grains and form intermetallic compounds with Fe impurities in the alloy, thus purifying the melt.

[0026] Zn is often combined with Al to improve room temperature strength. Zn can lower the boiling point of magnesium alloys and improve material properties through solid solution strengthening and / or precipitation strengthening. The high-strength lightweight alloys obtained after alloying can be used as structural materials.

[0027] A small amount of Ca can improve the metallurgical quality of magnesium alloys, reduce oxidation during the heat treatment of molten metal and castings, refine alloy grains, and improve the creep resistance of alloys.

[0028] Adding yttrium (Y) can strengthen magnesium alloys through solid solution treatment, refine the dendritic structure of the alloy, and play a positive role in the dispersion strengthening of precipitated products.

[0029] In particular, this invention employs a high-ignition-point modification method for magnesium alloys, using Ca and Y elements as raw materials for the magnesium alloy. Ca is the most effective element for inhibiting the oxidation and combustion of magnesium alloys. Adding Ca to Mg-Zn alloys can form high-melting-point compounds, thereby improving the high-temperature performance of the alloy. Furthermore, Ca also refines the grain size, improving the machinability of Mg-Zn alloys, and simultaneously enhances the corrosion resistance of the alloy by forming a protective oxide film on the surface. The addition of Y element also improves the oxidation resistance of magnesium alloys. Studies on the effects of oxidation characteristics on Mg-Ca-Y alloys show that the oxide layer on the surface of this ternary alloy melt has stronger protective properties and higher oxidation resistance than binary alloys.

[0030] Furthermore, this invention adds Ca and Y elements to the Mg-Zn alloy to increase its ignition point. The addition of Ca and Y elements forms a dense and thick oxide film on the surface, effectively blocking the melt from air. The solid solution of Ca and Y elements significantly improves the stability of the alloy's second phase. Ca enhances oxidation resistance by forming a dense oxide layer, with the outermost layer being CaO and the middle layer being a composite oxide film of CaO and MgO. This layer hinders the diffusion of oxygen from the external air into the molten metal, thus preventing internal oxidation reactions. At high temperatures, a dense and stable Ca-containing oxide film forms outside the magnesium alloy matrix. The larger film area of ​​this oxide film plays a crucial role in increasing the ignition point.

[0031] The preparation method of the high-strength, high-ignition-point magnesium alloy of the present invention includes the following steps:

[0032] 1) Smelting and casting

[0033] The alloy liquid billet is obtained by melting, stirring, slag removal and refining in a protective gas according to the above composition at a melting temperature of 720-750℃. During the preparation of the billet by melting, a mixed atmosphere of CO2 and SF6 with a ratio of (90-99):1 is used for protection. The alloy liquid billet is poured at 700-720℃ to obtain a cast alloy ingot.

[0034] 2) Heat treatment

[0035] The cast magnesium alloy ingot was heat-treated and homogenized at 460-500℃ for 3-6 hours. After heat treatment, the oxide scale on the surface of the cast magnesium alloy ingot was removed.

[0036] 3) Hot working

[0037] The cast magnesium alloy ingot is first extruded to obtain magnesium alloy billet with an extrusion ratio of 2 to 5; the magnesium alloy billet is then extruded a second time with an extrusion ratio of 9 to 25 to obtain magnesium alloy profile.

[0038] Preferably, the raw materials for preparing the magnesium alloy in step 1) are industrial pure magnesium ingots, industrial pure Al, industrial pure Zn, high-purity Mg-20Mn master alloy, high-purity Mg-20Ca master alloy, and high-purity Mg-30Y master alloy. Before batching, the oil stains, oxide scale, etc. on the surface of the raw materials are removed, and then the materials are weighed and batched according to the designed alloy composition.

[0039] Preferably, in step 1), the smelting time of the pure magnesium is 15 to 30 minutes.

[0040] Preferably, in step 1), the pouring is carried out after waiting 15 to 30 seconds until the temperature of the molten metal drops to 700 to 720°C.

[0041] Preferably, in step 2), the diameter of the cast alloy ingot is 85-90 mm and it has a riser. The surface of the ingot has an oxide layer. Before extrusion, the riser is cut off and the oxide scale is removed by machining.

[0042] Preferably, in step 3), the material is preheated at 320–380°C for 30–60 min before the first and second extrusions.

[0043] Preferably, in step 3), the cast magnesium alloy ingot is subjected to a first extrusion to obtain a magnesium alloy billet, the extrusion temperature is 320-380℃, and the extrusion ratio is 2-5; the second extrusion is carried out at 320-380℃, the extrusion ratio range of the second extrusion is 9-25, and the extrusion speed is 2-5 mm / s.

[0044] This invention removes impurities from the raw materials and oxidation from the molten metal during the melting process through refining, thereby obtaining a high-purity molten alloy. During the smelting and billet preparation process, a protective atmosphere of CO2 and SF6 in a ratio of (90-99):1 is used to remove air from the crucible and reduce oxidation on the surface of the molten metal during smelting.

[0045] Preferably, during melting, pure magnesium is melted first, followed by the addition of pure Al, pure Zn, Mg-20Mn master alloy, Mg-20Ca master alloy, and Mg-30Y master alloy. To further reduce element loss during smelting, the melt temperature is 720–750°C when the alloys are added.

[0046] Preferably, after all the alloy ingredients are melted, the mixture is allowed to stand for 3–5 minutes, and then argon gas is introduced for refining for 2 ± 1 minutes. After refining, the mixture is allowed to stand for 5–10 minutes.

[0047] Wait 15-30 seconds before pouring the molten metal. When the temperature of the molten magnesium alloy in the crucible drops to 700-720°C, remove the surface slag. Through these operations, remove as many impurity elements as possible from the alloy and reduce the degree of oxidation of the melt.

[0048] During pouring, it is essential to ensure the stability and continuity of the melt, guarantee complete filling, and pour into a cylindrical mold with a diameter of 85–90 mm, taking care to prevent slag from falling into the mold. During the pouring process, a mixture of SF6 and CO2 gas should be continuously used to protect the molten metal, reducing the degree of oxidation of the alloy during cooling and solidification.

[0049] Preferably, the present invention uses graphite oil to lubricate the die cylinder during extrusion, thereby reducing the frictional resistance during extrusion and ensuring smooth extrusion.

[0050] The billet from the first extrusion is held at 350℃ for 30 minutes, and then subjected to a second extrusion at 320-380℃. The second extrusion ratio is between 9 and 25, and the extrusion speed is between 2 and 5 mm / s. Graphite oil is used to lubricate the die cylinder during extrusion. After extrusion, the billet is cooled to room temperature.

[0051] The beneficial effects of this invention are:

[0052] This invention requires only the addition of trace amounts of Y element. By adjusting the Ca / Y element content ratio, the amount of Mg2Ca phase in the flame-retardant magnesium alloy is optimized, thereby achieving a synergistic improvement in the alloy's mechanical properties and ignition point, resulting in the alloy of this invention. Compared to traditional flame-retardant magnesium alloys, it has the advantages of low material cost and the ability to meet the needs of large-scale engineering applications.

[0053] The preparation method of this invention is simple. Compared with a single extrusion process, the distribution of Mg2Ca and MgZn2 phases in the magnesium alloy can be further controlled through a two-stage extrusion process, forming fine and dispersed reinforcing phases and improving its mechanical properties. The resulting extruded magnesium alloy material has good room temperature mechanical properties and high ignition point, with a tensile strength of up to 367 MPa, a yield strength of up to 328 MPa, an elongation of up to 13%, and an ignition point of up to 807°C, which can meet the needs of modern industrial and transportation applications. Detailed Implementation

[0054] The embodiments of the present invention will be further described below with reference to specific examples. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0055] The composition of the high-strength, high-ignition-point magnesium alloy in this embodiment of the invention is shown in Table 1, with the balance being Mg and the total mass fraction of impurity elements being less than 0.2%. The parameters of the preparation method in this embodiment of the invention are shown in Table 2.

[0056] In the experimental examples of the present invention, the mechanical properties and ignition points of the high-strength, high-ignition magnesium alloys in Examples 1-9 and Comparative Examples 1-9 were tested respectively.

[0057] 1) Tensile strength test

[0058] The tensile specimen dimensions were designed according to the relevant requirements of the national standard GB / T 228.1-2010 "Metallic materials, tensile testing—Part 1: Tests at room temperature." All specimens were machined using a wire EDM machine and a lathe. Before the tensile test, the specimen surface was polished with fine sandpaper to achieve a certain degree of smoothness. The tensile test was conducted at room temperature, with a tensile rate of 1×10⁻⁶. -3 s -1 .

[0059] 2) Ignition point test

[0060] Ignition point test method: Cut a magnesium alloy extrusion rod into pieces approximately 10×10×10mm in size. 3 The volume should be such that the surface is free of obvious stains, blemishes, cracks or any other defects that would impair its use.

[0061] The sample was placed in a resistance furnace with a maximum temperature of 1000℃ for ignition point testing. The furnace temperature was controlled at a heating rate of 5℃ / min. The curve of sample surface temperature versus heating time was obtained. When the curve of sample surface temperature versus heating time showed an inflection point, the magnesium alloy sample produced white smoke and combustion occurred. The temperature corresponding to the inflection point of the curve was the ignition point of the magnesium alloy.

[0062] In summary, the test results of the tensile mechanical properties and ignition point properties of the magnesium alloys in Examples 1-9 and Comparative Examples 1-9 of the present invention are shown in Table 3.

[0063] The above experimental results show that, compared with the experimental results of Examples 1-3 and Examples 7-9, when the ratio of Ca to Y elements is 2-4, the higher the Y element content in the alloy, the higher the ignition point, and the tensile strength at room temperature also increases with the increase of Y element content. This indicates that the comprehensive performance of magnesium alloys tends to improve with the increase of Y element content.

[0064] The above experimental results show that, comparing the results of Examples 1-9 with those of Comparative Examples 1-6, the alloy exhibits the highest mechanical properties and ignition point when the Ca:Y ratio is 2-4. Conversely, when the Ca:Y ratio is 1.6 and 6, the mechanical properties decrease. A Ca:Y ratio of 2-4 significantly increases the alloy's ignition point and strength. Adding Ca to alloys is typically for high-temperature resistance; Ca significantly increases the ignition point without increasing cost. Rare earth element Y can purify metals, improve oxide film adhesion, enhance the oxidation resistance of magnesium alloys, increase the ignition point, refine the alloy microstructure, and improve mechanical properties. The heat resistance of the alloy can be improved by adjusting the appropriate Ca:Y ratio, with Ca increasing the ignition point and Y improving both the ignition point and mechanical properties.

[0065] The above experimental results show that, comparing the results of Examples 1-3 with those of Comparative Examples 7-8, the alloy exhibits better mechanical properties when the secondary extrusion ratio is in the range of 9-25. Comparative Examples 7 and 9 show that when the secondary extrusion ratio is small, the mechanical properties of the alloy do not improve significantly. Comparative Example 8 shows that when the extrusion ratio is 36, the extruded alloy rod develops annular cracks and fails. This is because the excessively large extrusion ratio increases the deformation resistance, leading to excessive local shear stress and crack formation. The high friction and slow flow at the edges of the extruded part, coupled with the rapid flow in the central region, generate additional tensile stress exceeding the material's critical shear stress, resulting in annular cracks.

[0066] The above experimental results show that, comparing the results of Examples 1-3 with those of Comparative Example 9, secondary extrusion can significantly improve the mechanical properties of the alloy. Examples 1-9 demonstrate that a higher secondary extrusion ratio results in better mechanical properties. In Examples 1-6 and Comparative Examples 7-9, the alloy element content was the same, and the alloy ignition point did not change significantly, indicating that different extrusion ratios have little impact on the ignition point of magnesium alloys. Therefore, the secondary extrusion ratio is a key factor in improving the mechanical properties of magnesium alloys, and there is no correlation between the extrusion ratio and the ignition point of magnesium alloys.

[0067] The above embodiments and comparative examples have provided examples of the present invention. However, the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions, and variations made by those skilled in the art within the scope of the present invention shall fall within the protection scope of the present invention.

[0068] Table 1 Unit: Weight Percentage

[0069]

[0070]

[0071] Table 2

[0072]

[0073]

[0074] Table 3

[0075]

[0076]

Claims

1. A high-strength, high-ignition-point magnesium alloy, comprising the following weight percentages: Zn 5.10~6.30%, Al 0.50~1.00%, Mn 0.15~0.35%, Ca 1.50~2.50%, Y 0.50~1.00%, with the balance being Mg and other unavoidable impurities, and simultaneously satisfying: Ca / Y = 2~4; and obtained by the following method, comprising: The magnesium alloy ingot is subjected to two extrusion processes to obtain the finished product. The first extrusion ratio is 2 to 5, and the second extrusion ratio is 9 to 25.

2. The high-strength, high-ignition-point magnesium alloy as described in claim 1, characterized in that, The balance is Mg and other unavoidable impurities.

3. The high-strength, high-ignition-point magnesium alloy as described in claim 1 or 2, characterized in that, The total mass fraction of the unavoidable impurity elements is less than 0.2%.

4. The high-strength, high-ignition-point magnesium alloy as described in claim 1 or 2, characterized in that, Zn 5.50~6.00%, and / or, Al 0.55~0.80%, and / or, Mn 0.20~0.30%, and / or, Ca 1.80~2.30%, and / or, Y 0.60~1.00%, by weight percentage.

5. The high-strength, high-ignition-point magnesium alloy as described in claim 3, characterized in that, Zn 5.50~6.00%, and / or, Al 0.55~0.80%, and / or, Mn 0.20~0.30%, and / or, Ca 1.80~2.30%, and / or, Y 0.60~1.00%, by weight percentage.

6. The high-strength, high-ignition-point magnesium alloy as described in claim 1 or 2, characterized in that, The microstructure of the high-strength, high-ignition magnesium alloy consists of grains smaller than 10 μm, Mg2Ca phase dispersed at grain boundaries, and fine MgZn2 phase within the grains.

7. The high-strength, high-ignition-point magnesium alloy as described in claim 3, characterized in that, The microstructure of the high-strength, high-ignition magnesium alloy consists of grains smaller than 10 μm, Mg2Ca phase dispersed at grain boundaries, and fine MgZn2 phase within the grains.

8. The high-strength, high-ignition-point magnesium alloy as described in claim 4, characterized in that, The microstructure of the high-strength, high-ignition magnesium alloy consists of grains smaller than 10 μm, Mg2Ca phase dispersed at grain boundaries, and fine MgZn2 phase within the grains.

9. The high-strength, high-ignition-point magnesium alloy as described in claim 5, characterized in that, The microstructure of the high-strength, high-ignition magnesium alloy consists of grains smaller than 10 μm, Mg2Ca phase dispersed at grain boundaries, and fine MgZn2 phase within the grains.

10. The high-strength, high-ignition-point magnesium alloy as described in claim 1 or 2, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

11. The high-strength, high-ignition-point magnesium alloy as described in claim 3, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

12. The high-strength, high-ignition-point magnesium alloy as described in claim 4, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

13. The high-strength, high-ignition-point magnesium alloy as described in claim 5, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

14. The high-strength, high-ignition-point magnesium alloy as described in claim 6, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

15. The high-strength, high-ignition-point magnesium alloy as described in claim 7, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

16. The high-strength, high-ignition-point magnesium alloy as described in claim 8, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

17. The high-strength, high-ignition-point magnesium alloy as described in claim 9, characterized in that, The high-strength, high-ignition-point magnesium alloy has a tensile strength ≥280MPa, a yield strength ≥250MPa, an elongation ≥8%, and an ignition point ≥780℃.

18. The method for preparing high-strength, high-ignition-point magnesium alloy according to any one of claims 1 to 17, characterized in that, Includes the following steps: 1) Smelting and casting The alloy liquid billet is obtained by melting, stirring, slag removal and refining the components according to any one of claims 1 to 17 in a protective gas, with a melting temperature of 720 to 750°C; during the melting and billet preparation process, a mixed atmosphere of CO2 and SF6 with a ratio of (90 to 99): 1 is used for protection; the alloy liquid billet is poured at 700 to 720°C to obtain a cast magnesium alloy ingot. 2) Heat treatment The cast magnesium alloy ingot was heat-treated and homogenized at 460~500℃ for 3~6h. After heat treatment, the oxide scale on the surface of the cast magnesium alloy ingot was removed. 3) Hot working The cast magnesium alloy ingot is first extruded to obtain magnesium alloy billet with an extrusion ratio of 2 to 5; the magnesium alloy billet is then extruded a second time with an extrusion ratio of 9 to 25 to obtain magnesium alloy profile.

19. The method for preparing high-strength, high-ignition-point magnesium alloy as described in claim 18, characterized in that, In step 1), the raw materials for preparing the magnesium alloy are industrial pure magnesium ingots, industrial pure Al, industrial pure Zn, high-purity Mg-20Mn master alloy, high-purity Mg-20Ca master alloy, and high-purity Mg-30Y master alloy. Before batching, the oil stains and oxide scale on the surface of the raw materials are removed, and then the materials are weighed and batched according to the designed alloy composition.

20. The method for preparing high-strength, high-ignition-point magnesium alloy as described in claim 18 or 19, characterized in that, In step 1), the smelting time for pure magnesium is 15-30 minutes.

21. The method for preparing high-strength, high-ignition-point magnesium alloy as described in claim 18, characterized in that, In step 3), both the first and second extrusions are preheated at 320~380℃ for 30~60 minutes.

22. The method for preparing high-strength, high-ignition-point magnesium alloy as described in claim 18 or 21, characterized in that, In step 3), the cast magnesium alloy ingot is subjected to a first extrusion to obtain a magnesium alloy billet. The extrusion temperature is 320~380℃ and the extrusion ratio is 2~5. The second extrusion is carried out at 320~380℃, the extrusion ratio of the second extrusion is between 9 and 25, and the extrusion bar speed is 2~5 mm / s.

23. The method for preparing high-strength, high-ignition-point magnesium alloy as described in claim 18, characterized in that, In step 1), the pouring is carried out after waiting 15 to 30 seconds until the temperature of the molten metal drops to 700 to 720°C.

Citation Information

Patent Citations

  • Flame retardant magnesium alloy with excellent mechanical properties, and preparation method thereof

    CN102712969A

  • Secondary hot-extrusion technology of AQ80M magnesium alloy profiles

    CN107177762A